Предмет: Математика,
автор: сабик8
(×+2)^3-(×-1)^3=9×^2+36
Ответы
Автор ответа:
0
x³+6x²+6х-(х³-3х²+3х-1)=9х²+36
х³+6х²+6х-х³+3х²-3х+1=9х²+36
х³+6х²+6х-х³+3х²-3х-9х²=36-1
3х=35
х=35/3
х=11 2/3
х³+6х²+6х-х³+3х²-3х+1=9х²+36
х³+6х²+6х-х³+3х²-3х-9х²=36-1
3х=35
х=35/3
х=11 2/3
Похожие вопросы
Предмет: Математика,
автор: kanajymabdyldaeva10
Предмет: Математика,
автор: aleksandraknestapina
Предмет: Математика,
автор: probrawlstarsibo
Предмет: Геометрия,
автор: kazik1999
Предмет: Математика,
автор: ButterFry